Implementasi Manajemen dan Digitalisasi Perpustakaan di Lembaga Pendidikan SMAN 13 Surabaya - Cahyani, Davina; Adni, Shofy; Kartika, Engga; Salsabila, Salma; Anggraini, Della; Rahmawati, Febiana; Amelia, Elsa; Fitria, Rezki (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2025)
This study discusses the implementation of library management and digitalization at SMAN 13 Surabaya in response to the advancement of information technology in education. The library’s digitalization is realized through the application of online cataloging (OPAC), online book borrowing and returning services, and the development of an e-book collection accessible exclusively to students. Additionally, the library organizes literacy programs such as "Read Books for Prizes" and the School Literacy Movement (GLS) to enhance students’ reading interest and digital literacy skills. The research adopts a qualitative method involving observation, interviews, and documentation to obtain valid data from library staff. The findings indicate that a clear organizational structure and collaboration with IT-savvy alumni support efficient and innovative library management. Systematic classification and cataloging facilitate collection searches, while digital services expand information access beyond physical and temporal boundaries. The digitalization of the library at SMAN 13 Surabaya has proven to improve management efficiency, strengthen the culture of digital literacy, and create a modern and inclusive learning environment. However, the limitation of online catalog access, which is restricted to the school environment, poses a challenge for broader digital literacy development, the digitalization of the library at SMAN 13 Surabaya serves as a strategic step in supporting educational transformation towards the digital era.